Neurological and psychological effects of long COVID in a young population: A cross-sectional study - Guido, Cristiana Alessia; Lucidi, Fabio; Midulla, Fabio; Zicari, Anna Maria; Bove, Elena; Avenoso, Federica; Amedeo, Ilaria; Mancino, Enrica; Nenna, Raffaella; De Castro, Giovanna; Capponi, Martina; Cinicola, Bianca Laura; et al. (Frontiers in Neurology, 2022)
Aim We evaluated the long-term clinical status of pediatric patients after testing positive for COVID-19. We hypothesized that there are similar symptoms to those that have been described in adults and children and that pediatric patients with neurophysiologic symptoms still present 3–5 months after infection have psychological consequences that interfere with their adaptive functioning. Method We recruited 322 COVID-19-positive pediatric patients, between 1.5 and 17 years old, from the outpatient clinic for COVID-19 follow-up. Neurological symptoms were analyzed at onset, after 1 month, and after 3–5 months. A psychological assessment with standardized questionnaires was also conducted to determine the impact of the disease. Results At the onset of COVID-19, 60% of the total sample exhibited symptoms; this decreased after 1 month (20%) but stabilized 3–5 months after disease onset (22%). Prevailing long-COVID neurological symptoms were headache, fatigue, and anosmia. In the 1.5–5-year-old subgroup, internalizing problems emerged in 12% of patients. In the 6–18-year-old subgroup, anxiety and post-traumatic stress showed significant associations with neurological symptoms of long COVID. Conclusions These data demonstrate that long COVID presents various broad-spectrum symptoms, including psychological and long-lasting cognitive issues. If not treated, these symptoms could significantly compromise the quality of life of children and adolescents.